DI-100 Comparison of antibiotic prescribing for paediatric lower respiratory tract infections in three paediatric hospitals in the UK, France and Latvia. (24th February 2014) - Sviestina, I; Aston, J; Lorrot, M; Prot-Labarthe, S; Angoulvant, F; Doit, C; Mozgis, D
Abstract : Background: The most common indications for antibiotic use in hospitalised children are lower respiratory tract infections (LRTI). The point prevalence survey (PPS) allows targets to be identified for quality improvement. Comparing antibiotic use between different countries may help identify successful initiatives that further rationalise treatment. Purpose: To compare antibiotic use for LRTI between three paediatric centres in the UK, France and Latvia to identify strategies to optimise treatment. Materials and methods: This PPS was a part of the Antibiotic Resistance and Prescribing in European Children project (ARPEC). It was conducted at three tertiary-care children's hospitals in Birmingham (UK), Paris (France) and Riga (Latvia) using ARPEC methodology during November 2012. Results: LRTI accounted for 19/211 (9.0%) of antibiotic prescriptions in Birmingham, 29/245 (11.8%) in Paris and 43/168 (26%) in Riga. The most common age group of patients with LRTI across all three sites was under 5 years making up 14/19 (74%) patients in Birmingham, 14/29 (48%) in Paris and 22/39 (56%) in Riga. 7 different antibiotics were prescribed for LRTI in Birmingham, 14 in Paris and 9 in Riga. The most commonly prescribed antibiotics were co- amoxicillin/clavulanic acid 5 (28% of prescriptions) and piperacillin/tazobactam 5 (28%) in Birmingham, amoxicillin 5 (17%) and amoxicillin/clavulanic acid 6 (21%) in Paris and, amoxicillin 13 (30%) and ceftriaxone 9 (21%) in Riga. In Birmingham 13 (68%) antibiotic prescriptions were for community acquired infections, in Paris 24 (83%) and 42 (98%) in Riga. Antibiotics were predominantly prescribed intravenously: 11 (58%) prescriptions in Birmingham, 16 (55%) in Paris and 36 (84%) in Riga. Conclusions: The PPS identified differences in antibiotic use in 3 hospitals and the high use of parenteral antibiotics in all hospitals. Further studies are required to determine the appropriateness of the choice of antibiotics in LRTI, the diversity of agents prescribed and the use of broad-spectrum antibiotic treatment. No conflict of interest.